(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The deictic shift theory supposes that fictional narration has various deictic fields as Galbraith (1995) explained. Deictic fields indicate a set of deictic expressions associated with a character, narrator, spatial, temporal and social relations. The study hypothesizes that readers can transit from one situation to another by shifting the deictic expressions. Thus, it indicates a psychological orientation to interpret the characters and events in the fictional world of the narrative text. The study aims to investigate and identify the deictic dimensions, identifying the most frequent deictic expression reflects the viewpoint in the narrative text. The results of the study show that the most prominent frequent deictic expression, namely: personal deictic shift which shows the narrator’s inner struggle against the world he lives in, then when he moves to the new world (in his dream) , there is a deictic shift which clarifies the social-relation with the other people in the new society. The personal deictic shift manifests the narrator’s new viewpoint towards the real world. Spatial and temporal deictic are closely related with the personal deictic expression.